Atrazine bound residues formation and dissipation in subtropical soil under swine wastewater application - Gonçalves, Morgana S. (2012)
The effects of swine wastewater on atrazine dissipation and formation of bound residues in subtropical clay soil were investigated in this study. The experiment was carried out in laboratory, under room conditions, where samples of Rhodic Hapludox soil received 168.61 mg kg-1 of atrazine and were incubated for 60 days in the following treatments: T1 (sterilized soil + swine wastewater), T2 (sterilized soil + distilled water), T3 (Non sterilized soil + swine wastewater) and T4 (Non sterilized soil + distilled water). The extractable residues and bound residues of atrazine were extracted and analyzed by high performance liquid chromatography. The results showed no effect of swine wastewater on atrazine dissipation. However, the addition of swine wastewater favored the increase of bound residues, which can increase the persistence of atrazine in the environment and reduce its bioavailability